2018
DOI: 10.1111/jam.14062
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages on dairy foods

Abstract: This review focuses on the impact of bacteriophages on the manufacture of dairy foods. Firstly, the impact of phages of lactic acid bacteria in the dairy industry, where they are considered enemies, is discussed. The sources of phage contamination in dairy plants are detailed, with special emphasis on the rise of phage infections related to the growing use of cheese whey as ingredient. Other topics include traditional and new methods of phage detection, quantification and monitoring, and strategies of phage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 152 publications
(160 reference statements)
0
47
0
Order By: Relevance
“…Conversely, high levels of non-pathogenic E. coli in raw milk cheeses may contribute to the development of desirable characteristics of some of these products (Zago et al, 2007). The main advantage of using phages as biocontrol agents against undesired bacteria in cheese is that the specificity of phage-host spare the microbiota responsible for infusing natural flavors from being killed during treatment (Pujato et al, 2018). Conversely, the narrow host range limits the use of a single-phage treatments and multiple phage species are often mixed into cocktails (Abedon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, high levels of non-pathogenic E. coli in raw milk cheeses may contribute to the development of desirable characteristics of some of these products (Zago et al, 2007). The main advantage of using phages as biocontrol agents against undesired bacteria in cheese is that the specificity of phage-host spare the microbiota responsible for infusing natural flavors from being killed during treatment (Pujato et al, 2018). Conversely, the narrow host range limits the use of a single-phage treatments and multiple phage species are often mixed into cocktails (Abedon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was the first step toward the control of the use of antibiotics in agro-food production, as it is a major source of bacterial resistance acquisition [ 87 ]. Phages were used to protect dairy products [ 88 ], fruits [ 89 ], vegetables [ 90 ], meat [ 91 ], and fish [ 92 ]. Developments in the utilization of phages as antimicrobial agents in plant and animal agriculture at the farm level are summarized in a recent review by Svircev et al [ 93 ].…”
Section: Bacteriophages In Bio-related Applicationsmentioning
confidence: 99%
“…The impedance data were analyzed by two methods, i.e., impedance variation analysis at fixed frequency and equivalent modeling of the impedance data. First, we analyzed the 100 mHz impedance variations obtained within the test and control experiment with respect to the 4 h value, when the bacteria were inoculated in the wells, as described in Equation (1).…”
Section: Phage Detectionmentioning
confidence: 99%
“…This is probably due to the fact that the lysed bacteria still absorb at 600 nm. Pujato et al (2018) observed that turbidity was only positive for 90% of a group of samples for which lysis plaques were observed on plaque assays [1]. This proves that even standard detection techniques are not always reliable, reinforcing the importance of the introduction of a new phage detection method.…”
Section: Phage Detectionmentioning
confidence: 99%
See 1 more Smart Citation